The accuracy and precision of acetabular implant measurements from CT imaging - Henckel, Johann; Ramesh, Angelika; Hothi, Harry; Richards, Robin; Di Laura, Anna; Hart, Alister (Frontiers in Bioengineering and Biotechnology, 2023)
The accuracy and precision of 3D-CT for the measurement of orthopaedic hip component position and orientation is yet to be established. We compared measurements of cobalt chrome acetabular components implanted into 2 different bony pelvic models between a coordinate measuring Faro arm and 3 different low dose CT images, including 3D-CT, 2D APP referenced CT and 2D scanner referenced CT. Intra-observer differences were assessed using the Intra-class correlation coefficient (ICC). The effect of imaging the pelvis positioned in 3 different orientations within the CT scanner was also assessed. The measured parameters were the angles of inclination and version. 3D-CT measurements were found to closely match the ‘true values’ of the component position measurements, compared with the 2D-CT methods. ICC analysis also showed good agreement between the coordinate measuring arm (CMA) and 3D-CT but poor agreement between the 2D scanner referenced method, in the results from two observers. When using the coordinate system of the CT scanner, the measurements consistently produced the greatest error; this method yielded values up to 18° different from the reference digitising arm. However, the difference between the true inclination and version angles and those measured from 3D APP CT was below half a degree in all cases. We concluded that low radiation dose 3D-CT is a validated reference standard for the measurement of acetabular cup orientation.